National Identity versus European Identity The Dimensions of Change Developing the Greek teachers’ European identity - Papaeconomou, Anthony (Preschool and Primary Education, 2014)
This study examines the attitudes of Greek teachers towards Europe in relation with their national identity. Because of the Greek debt crisis and Greece’s entry into the IMF and EFSM mechanisms, two successive studies were conducted using the same questionnaire (the first with 1036 and the second with 482 teachers from all over Greece in 2009 and 2011 respectively). A two-step cluster analysis was performed and four particular dimensions were identified. The statistical analysis showed that there is a shift away from a European orientation, a finding that is attributed to economic difficulties.